CHILDREN EDUCATION IN THE BOOK OF TARBIYATUL AULAD FIL ISLAM BASED ON ABDULLAH NASHIH ULWAN'S AND PHILOSOPHY OF EDUCATION PERSPECTIVES - Muhammad Tafiudin (Tadibia Islamika, 2021)
The purpose of this study is to determine the concept of children's education in the Book of Tarbiyatul Aulad Fil Islam which includes the basics of children's education according to Abdullah Nashih Ulwan, the goals of children's education, materials and methods of children's education according to Abdullah Nashih Ulwan. This research method uses a qualitative approach and the type of research used is library research. While in data collection the author uses the method of documentation. In analyzing the data the author uses qualitative data analysis type, then the data analysis that the author uses is a descriptive method. The results showed that the concept of Children's Education according to Abdullah Nashih Ulwan includes Basic Education which includes the Principles of Bonding in the form of Akidah and Spiritual Ties which emphasizes the balance between individual needs and community needs. The materials for Children's Education include: Nurturing the Noble Psyche, Maintaining the Rights of Others, Maintaining Supervision and Criticism of Children's Education Methods by Using Education by Example, Education with Customs, Education with Advice, Education with Attention/Supervision, and Education with Punishment.